2010
DOI: 10.1186/1759-2208-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of information-carrying polymers of mixed sequences from double stranded short deoxynucleotides

Abstract: Background: The "RNA World" hypothesis suggests that an early form of life on Earth was based on nucleic acid strands able to store genetic information and catalyze a wide range of reactions including those which lead to self-replication. For this hypothesis to be true there must exist an efficient process for creating RNA or RNA-like polymers of mixed sequences from short precursors, where these polymers have to be long enough to fold into catalytically active structures (at least 40 bases). Results: We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Furthermore, it is interesting to note that recently, an invitro "implementation" of the binary polymer model was realized [17], where the food set consists of dinucleotides such as CA and TG, which can be interpreted as 0s and 1s in the binary model [18]. The authors conclude that "different building blocks can be incorporated into the strand, promoting the formation of combinatorial libraries of oligonucleotides long enough to be folded into specific catalytically active structures and to potentially form initial autocatalytic sets" [17]. This is a further indication that the binary polymer model (and its results) has direct (bio)chemical relevance, including in the context of origin of life studies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, it is interesting to note that recently, an invitro "implementation" of the binary polymer model was realized [17], where the food set consists of dinucleotides such as CA and TG, which can be interpreted as 0s and 1s in the binary model [18]. The authors conclude that "different building blocks can be incorporated into the strand, promoting the formation of combinatorial libraries of oligonucleotides long enough to be folded into specific catalytically active structures and to potentially form initial autocatalytic sets" [17]. This is a further indication that the binary polymer model (and its results) has direct (bio)chemical relevance, including in the context of origin of life studies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Even though this model already has a fair amount of chemical realism (for example, some recent experiments are an almost literal chemical implementation of the binary polymer model [5]), a direct application to a real chemical system was still lacking. Here, we construct and analyze a formal model version of the recent experimental RNA replicator system [1], and show how this results in:…”
Section: Introductionmentioning
confidence: 99%
“…High levelso f adaptation and refinement have been achieved in studies on the in vitro evolution of polymerizing enzymes, [1][2][3] and it has been shown that genetici nformation can be stored in and recovered from alternative genetic polymers based on nucleic acid architectures not found in nature. [4] High-yieldinga nalytically powerful nonenzymatic polymerization methodologies have also been developed, [5][6][7][8][9][10][11][12][13] enabling in vitro studies on molecular evolution and supporting the Darwinian logics pioneered by Spiegelman. [14] Complex chemistries involved in the nonenzymatic polymerization of highenergy monomers to nucleic acids are well described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiencyo ft he polymerization reactioni sd etermined by the extento fp hosphate activation and the properties of the leaving group. High-yieldingt emplate-directed RNA syntheses are commonly performed with 5'-phosphorimidazoliden ucleosides [9][10][11][12][13][14][15][16] or one of the numerous variants thereof, [17,18] because imidazole and its derivatives are good leaving groups. These are all high-energyc ompounds that polymerizee fficiently,b ut the likelihood of their prebiotic availability and accumulationi s inverselyp roportionalt ot heir intrinsic stability and the elaborate nature of the chemistry necessary fort heir synthesis.…”
Section: Introductionmentioning
confidence: 99%